Dynamics and persistence of CYP2D6 inhibition by paroxetine - Juřica, J; Žourková, A (Journal of clinical pharmacy and therapeutics, 2013)
WHAT IS KNOWN AND OBJECTIVE: Paroxetine is both a substrate and an inhibitor of CYP2D6. The objective of the presented study was to determine the persistence of CYP2D6 inhibition after short term (6 weeks) and long term (18·7 ± 10·6 weeks) paroxetine treatment. METHODS: Two the studies consisted of 30 depressive/anxiety patients each. In the first study, patients were subdivided into three groups treated with paroxetine (A1), alprazolam (A2) and paroxetine + alprazolam (A3). After 6 weeks, all the patients (A1+A2+A3) were switched to alprazolam treatment; metabolic activity was evaluated at the beginning, after 6 weeks of paroxetine/alprazolam/alprazolam + paroxetine treatment (A1/A2/A3) and 4 weeks after the switch to alprazolam treatment (Week 0, 6, 10). In the second study patients on previous long term paroxetine treatment were subdivided into two groups treated with mirtazapine (B1) or paroxetine (B2); metabolic activity of CYP2D6 was evaluated at the beginning and after 6 weeks of therapy. RESULTS AND DISCUSSION: Metabolic ratio of dextromethorphan to dextrorphan has normalized in all subjects after 4 weeks of paroxetine wash out in the first study. In the second study, 6 weeks after paroxetine discontinuation, restoration of metabolic activity of CYP2D6 was observed in only five of eight originally poor metabolizers. WHAT IS NEW AND CONCLUSION: We conclude that a wash-out period of 4 weeks seems to be sufficient for CYP2D6 disinhibition after short-term paroxetine treatment (6 weeks). On the other hand, treatment with a CYP2D6 substrate less than 6 weeks after long-term paroxetine treatment (18·7 weeks on average) could result in elevated drug plasma levels and occasionally also in drug toxicity.
Keywords: dospělí; Cytochrome P-450 CYP2D6 Inhibitors; alprazolam; paroxetin; Female; inhibitory cytochromu P450 CYP2D6; dextromethorfan; úzkost; Adult; mladý dospělý; ženské pohlaví; Adolescent; CYP2D6; dextrorfan; lidé; Alprazolam; dvojitá slepá metoda; disinhibition; Cytochrome P-450 CYP2D6; Anxiety; paroxetine; Double-Blind Method; Male; Aged; Young Adult; Dextrorphan; cytochrom P-450 CYP2D6; lidé středního věku; deprese; Paroxetine; senioři; mužské pohlaví; Dextromethorphan; Depression; Middle Aged; mladiství; Humans